Do Supply Chain Capabilities have an Impact on Firm Performance? A Case of the Manufacturing Sector in Gauteng Province - Mpho Tlale; Johan van der Westhuizen; Elizabeth Chinomona (African Journal of Inter-Multidisciplinary Studies, 2022)
Rapid technological growth, consumer fulfillment, shorter product life cycles, and more penetrating international competition define the business environment nowadays. The new competitive environment has required companies to acquire new ways of effectively pursuing a competitive advantage, since the competitive advantage of a firm now depends on operational efficiency and productivity across its functional areas. The main purpose of this research was to study the relation amongst supply chain capabilities (supply chain network design, supply chain information capabilities, and supply chain integration) and supply chain agility on firm performance in the Gauteng province’s manufacturing sector in South Africa. Structured questionnaires were circulated to different manufacturing firms in the Gauteng province. Data was analysed using SPSS and AMOS 26.0 software. Results showed that the level of firm performance in the manufacturing sector is dependent upon the effectiveness of supply chain capabilities and the existence of a sound long-term relationship between partners in the supply chain. Manufacturing managers and proprietors may be able to enhance the levels of firm performance by making improvements to supply chain technologies and improving supply chain agility by cultivating long-lasting sound relationships with key suppliers and customers.